Влияние зернового состава заполнителя на свойства низкоцементных огнеупорных бетонов - Шевцов, Р. Н.; Рябов, И. Д.; Онасенко, Ю. А.; Пилипчатин, Л. Д. (НТУ "ХПИ", 2010)
Вивчено вплив зернового складу шамотного заповнювача на показники властивостей низькоцементних вогнетривких бетонів в інтервалі температур 350 – 1300 °С та оптимізований вміст зерен фракції 6 – 3 мм і 3 – 0 мм. Виготовлено дослідну партію низькоцементних вогнетривких бетонних виробів оптимального складу і проведені їх випробування у різних теплових агрегатах.

Experimental researches have been conducted to study the influence of granularity fireclay aggregate on the propertes low – cement refractory concrete in interval of the temperature 350 – 1300 °С and was optimized contents aggregate fractions 6 – 3 mm and 3 – 0 mm. Organized test concrete product made with use of the optimum the composition aggregate organized their test in different heat unit.
Keywords: плотная упаковка зерен; характеристики бетонных масс; низкопористая структуры бетона; низкоцементные шамотные бетоны; зерновой состав заполнителя; шамотный огнеупорный бетон